ANALISIS YURIDIS ATAS SK PNS YANG DIJADIKAN AGUNAN DALAM PERJANJIAN KREDIT PERBANKAN DITINJAU DARI UNDANG-UNDANG NOMOR 10 TAHUN 1998 TENTANG PERBANKAN (STUDI PADA PT. BANK SUMUT IMAM BONJOL MEDAN) - LIA HARTIKA (PREMISE LAW JURNAL, 2016)
It is totally true that the credit given by the banks has risks. Therefore a bank must concern with the principles for resposible lending. To reduce those risks, a bank should convince themselves that the debtor is able to pay its obligations in accordance with the agreement. It is an important factor that must be considered by the bank. So, before giving a credit, banks should do some assessments of the character, capability, collateral and business prospects of the debtor. If those elements have been able to convince the lender, a bank just asks the principal guarantee, without any additional guarantee from the debtor like valuable papers in which the inherent right charged, such as shares, stocks, the decree of civil servants (SK PNS) or the decree of pension, and other documents. Although SK PNS is not a transferable object (which has the value of the redirects), but in the developments of the banking practice, some banks accept it as credit guarantee because it has economical value. The problems discussed in this research were what the position of SK PNS as  guarantee credit when it becomes the legal basis of banking credit was, what the legal consequences and accountability of civil servants over the collateralized SK PNS in credit agreements if the civil servants was fired was, and what the role of insurance companies in solving problems of credit insurance claims which the collareal was only SK PNS was.To answer those problems, this reasearch uses descriptive analytical method which intented to get the detailed description sistematically about this research’ problems. Based on the description, data analysis was expected to answer the problems. Keywords: Guarantee, Credit, Banking, SK PNS